Contributions of a Social Justice Language Teacher Education Perspective to Professional Development Programs in Colombia - Ana María Sierra Piedrahita (Universidad Nacional de Colombia, 2016)
In this article, the author discusses the social justice language teacher education perspective and how it can help language teachers to develop a political view of their work and effect change inside and outside their particular school contexts. To do this, she briefly analyzes various professional development programs for teachers of English in public schools in one city in Colombia to determine how these have or have not contributed to the development of a political perspective in teachers. Finally, she discusses what the implementation of such perspective requires, provides some examples to illustrate how it may look in practice, and discusses some implications for different stakeholders.